Arbitration, the World Trade Organization, and the Creation of a Multilateral Investment Court. (24th August 2021) - Bjorklund, Andrea K
Abstract: The proliferation of international tribunals has reached the investment sphere. The European Union and its treaty partners have included an investment court system in the four individual investment agreements they have negotiated since the European Union took competence over foreign direct investment with the passage of the Lisbon Treaty. The United Nations Commission on International Trade Law (UNCITRAL), with the European Commission's encouragement, is considering reform of investor-state arbitration with the front runner for reform the establishment of a multilateral investment court. Yet trade and investment law seem to be an oddly inverse relationship when it comes to preferred modes of dispute settlement. In the trade law realm, the survival of the 'crown jewel' of the World Trade Organisation (WTO)—its Dispute Settlement Body is uncertain. The appellate body has recently come in for special opprobrium. Arbitration is one of the suggested alternatives should existing dispute settlement procedures cease to function. Thus, in the investment law sphere, arbitration is apparently more and more disfavoured, and the preferred alternative is some kind of standing body with the pièce de résistance—an appellate body—at its apex. Why are these two regimes asynchronous? I hypothesize that states favour judicialization of disputes in the abstract but have reservations once judicialization becomes more concrete. Judicial or quasi-judicial decisions are hard for individual states to ignore or discredit, yet states have difficulty organizing multilateral responses to decisions they dislike.